The effect of overminus prescription on positive fusional vergence value and accommodation amplitude after watching video at 6 metre - Amer Hamzah, Nur Shazliyana; Ithnin, Mohd. Hafidz (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2020)
Introduction: The study aimed to investigate the effect -1.00 DS overminus prescription on positive fusional vergence (PFV) and accommodation amplitude (AA) after watching video at 6m. Method: Thirty normal participants without binocular vision anomalies (23.50 ± 1.50 years) were involved in this quasi-experimental study. All subjects wore additional -1.00 DS on the spectacle prescription for 15 minutes while watching video at 6m. The distance (6m) and near (40cm) PFV and AA were measured before and after 15 minutes watching video at 6m with the overminus prescription. Results: The result demonstrated the right eye (RE) AA reduced significantly (p<0.05) while the reduction on the left side was insignificant (p> 0.05). The changes of near and distance PFV was found insignificant (p> 0.05) after 15 minutes watching video at 6m with overminus prescription. Conclusion: Overminus prescription of -1.00DS for 15 minutes at distance fixation that presented in this study reduced the ability of accommodation. There were no changes in vergence system after intervention of -1.00 DS overminus prescription for 15 minutes at 6m.